End-tidal carbon dioxide monitoring during bag valve ventilation: the use of a new portable device - Lindström, Veronica (BioMed Central, 2010)
BACKGROUND: For healthcare providers in the prehospital setting, bag-valve mask (BVM) ventilation could be as efficacious and safe as endotracheal intubation. To facilitate the evaluation of efficacious ventilation, capnographs have been further developed into small and convenient devices able to provide end- tidal carbon dioxide (ETCO(2)). The aim of this study was to investigate whether a new portable device (EMMA™) attached to a ventilation mask would provide ETCO(2 )values accurate enough to confirm proper BVM ventilation. METHODS: A prospective observational trial was conducted in a single level-2 centre. Twenty-two patients under general anaesthesia were manually ventilated. ETCO(2 )was measured every five minutes with the study device and venous PCO(2 )(PvCO(2)) was simultaneously measured for comparison. Bland- Altman plots were used to compare ETCO(2, )and PvCO(2). RESULTS: The patients were all hemodynamically and respiratory stable during anaesthesia. End-tidal carbon dioxide values were corresponding to venous gases during BVM ventilation under optimal conditions. The bias, the mean of the differences between the two methods (device versus venous blood gases), for time points 1-4 ranges from -1.37 to -1.62. CONCLUSION: The portable device, EMMA™ is suitable for determining carbon dioxide in expired air (kPa) as compared to simultaneous samples of PvCO(2). It could therefore, be a supportive tool to asses the BVM ventilation in the demanding prehospital and emergency setting.